First Record of Coccinellid Beetles (Coleoptera: Coccinellidae) on Poplar, Populus deltoides from North India - Ahmad, Mukhtar; Jamal Ahmad, M. D.; Afroze, Shama; Mishra, R. K. (Indian Forester, 2001)
Association of nine coccinellid beetles with Poplar (Populus deltoides) was recorded first - time from Poplar nurseries, in Tarai region of Uttaranchal and Haryana. These include eight predacious species viz. Anegleis cardoni (Weise), Coccinella septempunctata Linnaeus, Hippodamia variegata (Goeze), Illeis cincta (Fabricius), Menochilus sexmaculatus (Fabricius), Micraspis discolor (Fabricius), Propylea japonica (Thunberg) and Rodolia fumida Mulsant found feeding on aphids and other small insect preys infesting on Poplar foliage. Another coccinellis, Epilachna vigintioctopunctata (Fabricius) was found to be a phytophagous species feeding on Poplar foliage. A key for easy identification of the recorded species has been incorporated.